Implementasi Metode Double Exponential Smoothing Untuk Memprediksi Indeks Pembangunan Manusia (IPM) Di Kabupaten Toraja Utara - Adistacia Caesara Ampang; Billy Eden William Asrul; M. Adnan Nur (Jurusan Teknik Elektro Fakultas Teknik Universitas Halu Oleo, 2023)
Abstract — The Human Development Index (IPM) is an indicator that explains how people can access development outcomes in obtaining human income, health and education. This study aims to make predictions on the Human Development Index (IPM) in North Toraja Regency using the Double Exponential Smoothing algorithm. The stages of this research began with collecting data obtained from observation, interviews and documentation. The research design used is UML which is designed in a structured manner consisting of use case diagrams, activity diagrams, sequence diagrams and class diagrams. The software used in building this system is PHP and MySql for database processing. The algorithm used is Double exponential smoothing to predict the Human Development Index in North Toraja Regency for the next few years using past data. In this case, the best alpha and beta values are 0.6 and 0.9. The results of calculating the accuracy between the prediction results and the actual data using the Mean Absolute Percetage Error (MAPE) each have a forecasting error value of 0.13% for the Health Index, for the education index of 0.55%, and for the Purchasing Power Index of 0.45 %. Based on the results of these predictions, the value of the Human Development Index (IPM) in North Toraja Regency for the following year is 69.48%. Keywords: Double Exponential Smoothing, Human Development Index, prediction, MAPE, North Toraja Regency